ANALISIS KELAYAKAN USAHA AYAM PEDAGING (Gallus Domesticus) DENGAN POLA KEMITRAAN DI DESA MANDIANGIN BARAT (Studi kasus pada Peternakan Ayam pedaging milik pak Katimin) - Zulipah Mahdalena; Rohansyah; Muhammad Agung Wahyudi (Chlorophyl, 2025)
This research aims to determine production costs, revenues, profits and feasibility of mr.Katimin broiler chicken business in west Mandiangin villige. This research method uses the case study method. The case study method is reaserch about a case where each prosess in carried out in detail, sharply and in depth. The case studies was a broiler chicken business with a patthership pattern. The result of the research obtained a total cost (production cost) of IDR.29.211,055/ month, the amount of revenue is IDR 110.772,230/ production period. The Profit obtained is IDR.13.624.730/production period, and the Fesiability obtained was 1.13. From the RCR value, it can be said that this partnership pattern broiler business is stillworth pursuing